USE OF INDUSTRIAL LAND IN AL-MAHMODIYA DISTRICT - Timman, Zamil L. (Humanities & Social Sciences Reviews, 2021)
Purpose of the study: The research aims to examine the impact of factors related to the spatial distribution of industries and determine their importance in controlling the economic activity of Mahmoudiyah City to determine the direction of the industry compass on the level of this district. There are different industry types in this city, including hand or small industry, such as spinning, knitting, and fancywork industry. As well as light industry, for example, woven, cane, building materials, wooden and metallic industry. Methodology: This research is of theoretical type, and the research method is descriptive-analytical, and the method of data collection is a library and has been done by referring to documents, books, and articles. Results: The results showed that more of these industries mentioned above are found in Al-mahmodiya center and Al-latefiya because found labor market and its nearly of consumed as well as increase of population with different skills hands lead to the stable economic and social case. There is a challenge in the provided modern machine and discontinue of electric current, leading to decreased production. Application: This study can be useful in the Studies of Industrial Geography. Novelty: This field study indicates that the industrial craft is affected by choosing the suitable place for industrial plants to reduce the pollution and noise ratio in the known industrial regions and describes one of the major problems that still exists is the return of land ownership.